Analysis of snorkeling Amed tourism object marketing strategy - Anggreni, Putri; Suartini, Ni Wayan (International research journal of management, IT and social sciences, 2021)
The purpose of this study was to determine the marketing strategy carried out by the manager of the Snorkeling Amed attraction and to find out the strengths, weaknesses, opportunities, and threats possessed by this tourism object and also to find out alternative strategies that can be used by the Snorkeling Amed attraction. The data analysis technique used is SWOT (Strength, Weakness, Opportunities, Threats) analysis. What is meant by this analysis is to identify the internal and external environment of Amed's snorkeling tourism object in a competitive climate with similar businesses operating in the same business field. A SWOT analysis covers the external environment and the internal environment. Environmental analysis is a process used to determine strengths, weaknesses, opportunities, and threats. In this SWOT analysis, a qualitative approach and a quantitative approach will be used. A qualitative approach is an analysis that is used without the use of numerical calculations but based on judgments or opinions and the basics that can support subjective decision making. While the quantitative approach is a way of analyzing data using the calculation of numbers or to support the process of analyzing the data.